2014
DOI: 10.1038/srep05529
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of red-capped mangabey tetherin: implication for the co-evolution of primates and their lentiviruses

Abstract: Primate lentiviruses including human immunodeficiency virus type 1 (HIV-1) and simian immunodeficiency viruses (SIVs) evolved through the acquisition of antagonists against intrinsic host restriction factors, such as tetherin. It is widely accepted that HIV-1 has emerged by zoonotic transmission of SIV in chimpanzee (SIVcpz), and that SIVcpz Nef protein antagonizes chimpanzee tetherin. Although Nef of SIVcpz shares a common ancestor with that of SIVrcm, an SIV in red-capped mangabey (Cercocebus torquatus), it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…To date, most of the relevant studies have reported that error-prone RNA viruses and lethal viruses (e.g., HIV and filovirus) exert selective pressure on their host proteins (17)(18)(19)(20)(21)(22)(23)(24)37). On the other hand, if a virus is not pathogenic to the host, adaptive mutations in host proteins would not be expected to occur (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most of the relevant studies have reported that error-prone RNA viruses and lethal viruses (e.g., HIV and filovirus) exert selective pressure on their host proteins (17)(18)(19)(20)(21)(22)(23)(24)37). On the other hand, if a virus is not pathogenic to the host, adaptive mutations in host proteins would not be expected to occur (13).…”
Section: Discussionmentioning
confidence: 99%
“…During the course of long-term viral selective pressures, some host restriction factors evolve rapidly, a process that is evidenced as a ratio of nonsynonymous to synonymous mutations in the host gene (the dN/dS ratio) that exceeds 1 (termed positive selection) (16). For example, host restriction factors against human immunodeficiency virus type 1 (HIV-1), including tripartite motif-containing protein 5-alpha (TRIM5␣) (17), apolipoprotein B mRNA editing enzyme catalytic polypeptidelike 3 G (APOBEC3G) (18), bone marrow stromal antigen 2 (BST2; also known as tetherin, CD317, and HM1.24) (19)(20)(21)(22), and SAM domain and HD domain 1 (SAMHD1) (23,24), have been reported to exhibit rapid evolution (dN/dS ratio of Ͼ1), likely due to the selective pressure exerted by HIV-1 infection. Regarding the coevolution of hepadnaviruses and host restriction factors, Abdul et al recently reported an evolutionary analysis of an HBV restriction factor, the Structural Maintenance of Chromosomes 5/6 (Smc5/6) complex (25), a complex originally identified based on its housekeeping function in genomic stability (26).…”
mentioning
confidence: 99%
“…Whatever they may be, the adaptations leading to control of the deleterious consequences of SIV infection in natural hosts are almost certainly the result of long-term coevolution between African hosts and their species-specific SIVs (Chahroudi et al, 2012; Fischer et al, 2012; Kobayashi et al, 2014; Ma et al, 2013; Pandrea and Apetrei, 2010). Here, we will review the current knowledge regarding SIV-infection in natural hosts, with an extra focus on the events surrounding transmission.…”
Section: Introductionmentioning
confidence: 99%
“…We co‐transfected these plasmids into HEK293T cells by using PEI Max (Polysciences, Warrington, PA, USA) and harvested the cells and viral particles from culture supernatants at 48 hr post‐transfection. The harvested samples were used for SDS‐PAGE/western blotting or lentiviral reporter assays as previously described . Briefly, we used the following antibodies for western blotting: an anti‐FLAG polyclonal antibody (Sigma, St Louis, MO, USA), an anti‐HA antibody (3F10; Roche, Indianapolis, IN, USA), an anti‐FIV p27 Capsid antibody (PAK3‐2C1; Santa Cruz Biotechnology, Santa Cruz, CA, USA); an anti‐α‐tubulin antibody (DM1A; Sigma) and an anti‐VSVg antibody (P5DA; Roche).…”
mentioning
confidence: 99%